Which banks are more risky? The impact of loan growth and business model on bank risk-taking - Matthias Köhler (Deutsche Bundesbank, 2012)
In this paper, we analyze the impact of loan growth and business model on bank risk in 15 EU countries. In contrast to the literature, we include a large number of unlisted banks in our sample which represent the majority of banks in the EU. We show that banks with high rates of loan growth are more risky. Moreover, we find that banks will become more stable if they increase their non-interest income share due to a better diversification of income sources. The effect, however, decreases with bank size possibly because large banks are more active in volatile trading and off-balance sheet activities such as securitization that allow them to increase their leverage. Our results further indicate that banks become more risky if aggregate credit growth is excessive. This even affects those banks that do not exhibit high rates of individual loan growth compared to their competitors. Overall, our results indicate that differences in the lending activities and business models of banks help to identify risks, which would only materialize in the long-term or in the event of a shock.
Keywords: G20; G21; G28; 330; banks; risk-taking; business model; loan growth